Estudo da autonomia pessoal de usuários em início de tratamento por uso de drogas ilícitas no centro de atenção psicossocial álcool e drogas de São Carlos, SP - Silva, Adriano André da (2016)
The biopsychosocial phenomenon of drug use becomes a challenge to the health promotion because of the multitude of factors involved; among them, the subject's autonomy. Aiming to identify and understand a set of aspects related to personal autonomy for the use and search for treatment because of disorders related to use of illicit drugs, we used the clinicalqualitative Method and interpretive interactionism to investigate the people's autonomy in the beginning of the treatment at CAPS- AD São Carlos, SP. The data obtained through nondirected interviews done with ten of these subjects were organized into thematic categories, which the content analysis showed that some people had a voluntary action, both for the drug use and for the search for treatment. However, others did not recognize their volitional intention for drug or had their self-care autonomy impaired. On the other hand, it was observed that the reflection about the use condition itself seems to move people to search for treatment. Therefore, it is important to consider that the subject's autonomy is crucial for both the determination by the use of drugs and for seeking treatment and self-care, although it may be impaired in some circumstances. This implies that the treatment project for the care of people who use illegal drugs need to consider the reflections and decisions of the subject itself about their living conditions and the maintenance of the use factors, as well as the possibility of choice and improved quality of life.